The social customer : how brands can use social CRM to acquire, monetize, and retain fans, friends, and followers - Metz, Adam. (New York : McGraw-Hill, 2012)
'Customers have changed--and you must, too, if you want to stay relevant. By now, business leaders fully understand that customers empowered by social media are fundamentally changing the way they interact with the brands they consume. What they've missed, however, is that this isn't just a marketing issue. It's an organizational issue. And those who plan to compete in the future must develop a business strategy that places major emphasis on appealing to the Social Customer.Succeeding in the new social world of business is much more than a matter of setting up Twitter accounts, understanding the mechanics of viral campaigns, or responding quickly to customer complaints in social forums before they swell out of control. Rather, it's a matter of re-engineering an entire division or organization: it's about social customer relationship management that spans across the entire company: sales, marketing, fulfillment, management, and other departments. The Social Customer provides a strategic platform you can use to position your organizations to survive and thrive, as well as tactical resources to use in implementation. In short, it presents the next wave of social media strategy that all companies must adopt if they wish to find success in the future'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Customer relations -- Management; Branding (Marketing).